Coherent Transfer of Transverse Optical Momentum to the Motion of a Single Trapped Ion - Stopp, Felix; Verde, Maurizio; Katz, Milton; Drechsler, Martin; Schmiegelow, Christian T.; Schmidt-Kaler, Ferdinand (Physical Review Letters, 2022)
Using a structured light beam carrying orbital angular momentum, we demonstrate excitation of the center-of-mass motion of a single atom in the transverse direction to the beam's propagation. This interaction enables quantum control of atomic motion in all axes with a single beam direction, which leads to applications in quantum computing and simulations with ion crystals. Here we demonstrate all the key features required for these applications, namely, coherent dynamics and strong carrier suppression in a configuration with the ion centered in the beam, which allows for single ion addressing and also provides robustness against pointing instabilities. To quantify transverse momentum transfer, we observe coherent dynamics on the sidebands of the S1/2 to D5/2 transition near 729 nm of a singly charged Ca+40 ion, cooled near the ground state of motion in the 3D harmonic potential of a Paul trap, and placed at the center of a first-order Laguerre-Gaussian beam. Exchange of quanta in the perpendicular direction to the beam's wave vector k is observed with a centered vortex shaped beam, together reduction of the parasitic carrier excitation by a factor of 40. This is in sharp contrast to the vanishing spin-motion coupling at the center of the Gaussian beam. Further, we characterize the coherent interaction by an effective transverse Lamb-Dicke factor η⊥exp=0.0062(5) which is in agreement with our theoretical prediction η⊥theo=0.0057(1).
CRIS-Team Scopus Importer:2023-03-27